Genetic diversity of morphological, biochemical and mineral traits in Indian onion (Allium cepa) genotypes - CHANDEL, RAHUL; SINGH, SHRAWAN; KUMAR, AMRENDER; TAAK, YASHPAL; KHAR, ANIL (The Indian Journal of Agricultural Sciences, 2024)
The present study was carried out during 2021 and 2022 at ICAR-Indian Agricultural Research Institute, New Delhi to evaluate the diversity among 83 onion (Allium cepa L.) genotypes utilizing morphological, biochemical, and mineral profiling. Substantial genetic variances were observed across all the investigated traits. Traits such as bulb phenol content, bulb pyruvic acid content, neck thickness, average bulb weight, iron, zinc, and sulphur recorded high genotypic coefficient of variance (GCV) and phenotypic coefficient of variance (PCV) values, whereas plant height, total soluble solids, marketable yield, dry matter, and calcium had moderate GCV as well as PCV values. High heritability was observed for all traits except for iron content, which ranged from 98.32% (bulb phenol content) to 37.93% (Iron). Principle Component Analysis (PCA) extracted 5 principal components (PC1–PC5), accounting for a cumulative variance of 59.88%. The primary contributors to PC1 were average bulb weight, marketable yield, and equatorial diameter, while PC2 was primarily influenced by iron content, bulb pyruvic acid content, and neck thickness. On the basis of Euclidean distance and Ward’s D2 analysis, all the genotypes were grouped into three clusters. Cluster 1 showed the highest values for dry matter, iron and zinc content. Cluster 2 consisted of genotypes with higher values for plant height, polar diameter, average bulb weight, calcium, potassium, and sulphur content, whereas it showed lower values for neck thickness. Cluster 3 exhibited higher values for equatorial diameter, total soluble solids and marketable yield. Greater genetic diversity offers breeders enhanced opportunities to identify promising genotypes for selection or utilization as parents in hybrid breeding programmes.